Survey: Is there a Caribbean discourse today? - The Editor (Karib)
As the first issue of 'Karib' is dedicated to the concept of the archipelagic, we have invited scholars to answer 'one' or 'both' of the following questions: “Is the idea of a Caribbean discourse relevant in your work?” And: ”Do you think that there is a current Caribbean discourse, and if so, how has it evolved since the publication of Glissant’s 'Le Discours antillais' in 1981?” The idea behind such an invitation has been to shed light upon the various ways in which the Caribbean region may be (re-)thought today, and – by extension – to discuss the current status of Glissant’s seminal work from 1981. The invited scholars have been given liberty both concerning language and length of answers. We hereby present their views in alphabetical order.